The Effectiveness of Using WordPress-Based Digital Invitations in Social Event Marketing - Aini, Qurotul; Santoso, Nuke Puji Lestari; Mustofa, Kenny Ilyas; Apriani, Desy (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
Digital marketing plays an important role in enhancing the promotion of social events in the digital era. In an effort to reach a wider audience, WordPress-based digital invitations are one of the potential tools to support marketing effectiveness. This study aims to analyze the extent to which the use of WordPress-based digital invitations can help social event organizers increase audience participation and engagement. This research uses a quantitative descriptive method with data collection through a survey of social event organizers and analysis of traffic and engagement data from the WordPress platform. The data collection process was conducted to understand the impact of WordPress features, such as flexible design, SEO optimization, and social media integration, on social event marketing success. The results showed that WordPress-based digital invitations significantly increased the number of event participants, the level of audience engagement, as well as the perceived professionalism of the event. These findings indicate that WordPress can be an effective strategic tool in digital marketing for social events. In conclusion, WordPress is a platform that can support social event organizers in designing more effective marketing strategies, especially by leveraging its features to optimize the appeal of digital invitations. This research provides practical insights for event organizers and opens up opportunities for further research in similar areas.